Etnobotânica e conservação on farm de mandioca (Manihot esculenta Crantz) na agricultura de pequena escala no Estado de Mato Grosso, Brasil - Oler, Juliana Rodrigues Larrosa [UNESP]; Amorozo, Maria Christina De Mello [UNESP] (Universidade Católica Dom Bosco, 2017)
The present study investigates the role of traditional community Luzia (CL) and the rural settlement Banco da Terra (BT) (Mato Grosso State, Brazil) in on farm conservation of cassava, through socioeconomic census, ethnobotanical survey, identification of local varieties and participant observation. In CL was found higher ethnobotanical knowledge, although BT has presented a higher income (39 BT and 30 CL) and diversity (H' = 3.24 BT and 3.01 CL). The low similarity between collections reveal the complementarity of areas in the on farm maintenance of the agrobiodiversity.

El presente estudio investigó el papel de la comunidad tradicional Luzia (CL) y del asentamiento rural Banco de la Tierra (BT) (Estado de Mato Grosso, Brasil) en la conservación on farm de yuca, a través de censo socioeconómico, levantamiento etnobotánico, identificación de las variedades locales y observación participante. En la CL se encontró mayor conocimiento etnobotánico, aunque el BT presentó mayor riqueza (39 BT y 30 CL) y diversidad (H' = 3,24 BT e 3,01 CL). La baja similitud entre los acervos revela la complementariedad dos lugares en la manutención on farm de la agrobiodiversidad.

La présente étude a porté sur le rôle de la communauté traditionnelle Luzia (CL) et l'assentamento « Banco da Terra » (BT) (Mato Grosso, Brésil) dans la conservation on farm de manioc, par le biais de recensement socio-économique, la collecte ethnobotanique, l'identification des variétés locales et l'observation participante. À la CL a été trouvé la plupart des connaissances ethnobotaniques, bien que le BT a eu une plus grande richesse (39 BT et 30 CL) et une diversité (H' = 3,24 BT et 3,01 CL). La faible similitude entre les collections révèle la complémentarité entre les locaux pour la conservation on farm de l'agrobiodiversité.

Este estudo investigou o papel da comunidade tradicional Luzia (CL) e do assentamento rural Banco da Terra (BT) (Mato Grosso, Brasil) na conservação on farm de mandioca, através de censo socioeconômico, levantamento etnobotânico, identificação das variedades locais e observação participante. Na CL foi encontrado maior conhecimento etnobotânico, embora o BT tenha apresentado maior riqueza (39 BT e 30 CL) e diversidade (H' = 3,24 BT e 3,01 CL). A baixa similaridade entre os acervos revela a complementaridade dos locais na manutenção on farm da agrobiodiversidade
Ethnobotany and on farm conservation of cassava (Manihot esculenta Crantz) in small scale agriculture in the State of Mato Grosso, Brazil
Etnobotánica y conservación on farm de yuca (Manihot esculenta Crantz) en la agricultura a pequeña escala en el Estado de Mato Grosso, Brasil
Keywords: rural settlement; traditional community; agrobiodiversity; assentamento rural; comunidade tradicional; agrobiodiversidade